2021
DOI: 10.26464/epp2021025
|View full text |Cite
|
Sign up to set email alerts
|

Review of ionospheric irregularities and ionospheric electrodynamic coupling in the middle latitude region

Abstract: This paper briefly reviews ionospheric irregularities that occur in the E and F regions at mid‐latitudes. Sporadic E (ES) is a common ionospheric irregularity phenomenon that is first noticed in the E layer. ES mainly appears during daytime in summer hemispheres, and is formed primarily from neutral wind shear in the mesosphere and lower thermosphere (MLT) region. Field‐aligned irregularity (FAI) in the E region is also observed by Very High Frequency (VHF) radar in mid‐latitude regions. FAI frequently occurs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 119 publications
(198 reference statements)
0
12
0
Order By: Relevance
“…The SLT theory also showed that ion caviton collapse could be generated, which is related to oscillating two-stream instability. The irregularities can be excited in turbulence process with meter scale, which is smaller than in Natural excitation process with kilometer scale (Liu et al, 2021). The irregularities can effect the wave propagation (Jiang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The SLT theory also showed that ion caviton collapse could be generated, which is related to oscillating two-stream instability. The irregularities can be excited in turbulence process with meter scale, which is smaller than in Natural excitation process with kilometer scale (Liu et al, 2021). The irregularities can effect the wave propagation (Jiang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…There are several impact factors that are responsible for the occurrence of ionospheric irregularities [6,7]. Studies reveal that large number of ionospheric irregularities have variable patterns, such as sporadic E (Es), spread F, field-aligned irregularities (FAIs) and plasma bubbles.…”
Section: Introductionmentioning
confidence: 99%
“…The mid-latitudes ionospheric irregularities are found usually to be associated with atmospheric gravity waves and medium-scale travelling ionospheric disturbances (MSTID) [15,16]. Its major cause is attributed to Perkins instability [7,[17][18][19]. In this theory, a north-south electric field is present in addition to the east-west electric field, leading to the form of rising and falling sheets of ionization.…”
Section: Introductionmentioning
confidence: 99%
“…The Es layer modulated by KHI is numerically studied in a linear regime (Bernhardt, 2002), in which relatively weaker KHI can produce large amplitude modulation. The role of KHI mechanism has not been widely recognized yet (Choudhary et al., 2005; Liu et al., 2019, 2020, 2021; Patra et al., 2009). The nonlinear KHI mechanism generating the enhanced horizontal structure of Es layer is not clear.…”
Section: Introductionmentioning
confidence: 99%